PERAN KEPUASAN KERJA MEMEDIASI PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN HOUSEKEEPING DEPARTMENT FAVE HOTEL - Prawira, I Gusti Agung Gde Yoga; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 8 No 8 (2019), 2019)
Companies must be able to maintain employee performance to remain stable and even increase. Satisfied employees are effective and well-performing workers. The purpose of this study was to determine the direct effect of work stress and job satisfaction on employee performance, to determine work stress on employee job satisfaction, and to determine the effect of Job Satisfaction in mediating the effect of work stress on employee performance. The population in this study were 47 Fave Hotel Housekeeping Department employees. Sampling uses a saturated sample technique and the data was analyzed using path analysis techniques. The results showed that work stress has a negative and significant effect on job satisfaction and employee performance, namely the higher the level of work stress that employees have, the lower the job satisfaction and employee performance that will be formed within the employee. Job satisfaction has a positive and significant effect on employee performance. This means that the higher job satisfaction felt by employees, the higher the performance of employees that will be formed. Job satisfaction is positively and significantly mediates the effect of work stress on employee performance. Keywords : Job Satisfaction, Job Stress, and Employee Performance